Mercado de capitais brasileiro: discussão sobre a eficácia dos mecanismos de proteção dos acionistas minoritários não qualificados nos processos de IPO (Initial Public Offering) na Bovespa, no período de 2004 a 2007 - Silva, José Milton Almeida da (2009)
The central goal of this research was to increase the debating about efficacy from rules, legal actions and Corporate governance to protect the non qualified minority shareholders in the Brazilian IPOs (Initial Public Offering) programs. The theme has showed growing interest, because the number of personal investors and the Bovespa s (São Paulo Stock Exchange) IPO market has been in progress strongly. The event study was the methodology used to measure the abnormal returns in the portfolio s samples with between 23 and 98 shares from 106 IPOs going public in 2004-07, using de market price from January, 2004 to June, 2008. Further, four statistic tests were applied to detect if the speculative bubble dynamic affected the Bovespa from January, 1999 to June, 2008. The empiric results from event study evidenced the overpricing phenomenon measured from the offering price to the market price at the end of the first day of trading estimated between 4,80% and 9,26%, and a underpricing phenomenon in the sequel. The cumulative average abnormal returns, ruled out of the first day return, achieved -11,52% at the end of the 6º month, -16,60% at the end of the 12º month and -35,74% at the end of the 24º month, presented a underperfomance phenomenon with economic and statistic significance, widely documented by the academy, specially on the north American capital market. The empiric results from four statistic tests showed, with statistic significance, that speculative bubble dynamic affected the Ibovespa (Index of São Paulo Stock Exchange) in the period from January, 1999 to June, 2008. Thus, evidences were found of the minority shareholders that bought shares in the Bovespa s IPOs programs in the studied period were induced by market anomalies to overpay the share s portfolios. Consequently, the research suggests that actions to improve the rules, legal actions and Corporate governance is necessary to protect of the non qualified minority shareholders in the Brazilian capital market